2014
DOI: 10.1002/ijc.29384
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation and replication of miRNAs with disease stage and colorectal cancer‐specific mortality

Abstract: MiRNAs have been implicated in CRC development and associated with prognostic indicators such as disease stage and survival. Prognostic associations are often based on few individuals and imprecise. In this study, we utilize population-based data from 1141 colorectal cancer (CRC) cases to replicate previously reported associations between 121 miRNAs and disease stage and survival. The Agilent Human miRNA Microarray V19.0 was used to generate miRNA data following a stringent quality control protocol. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 49 publications
7
131
1
1
Order By: Relevance
“…Among them, cancer-related pathways, the PI3K-Akt signaling pathway, and the MAPK signaling pathway were the main pathways identified, which is consistent with our previous findings that B7-H4 inhibition has anti-tumor effects via multiple targets, including decreasing oncogenicity, inducing apoptosis, and decreasing Erk1/2 phosphorylation [8]. These results implyed that B7-H4-related miRNAs might significantly affect these pathways to contribute to tumorigenesis [24-26]. It was well-known that the PI3K-Akt and MAPK signaling pathways are involved in the processes of tumor cell apoptosis and tumor development [36, 37].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Among them, cancer-related pathways, the PI3K-Akt signaling pathway, and the MAPK signaling pathway were the main pathways identified, which is consistent with our previous findings that B7-H4 inhibition has anti-tumor effects via multiple targets, including decreasing oncogenicity, inducing apoptosis, and decreasing Erk1/2 phosphorylation [8]. These results implyed that B7-H4-related miRNAs might significantly affect these pathways to contribute to tumorigenesis [24-26]. It was well-known that the PI3K-Akt and MAPK signaling pathways are involved in the processes of tumor cell apoptosis and tumor development [36, 37].…”
Section: Discussionsupporting
confidence: 77%
“…Notably, miR-299-5p and miR-1284 were significantly up-regulated, while miR-21 and miR-335-5p was significantly down-regulated following B7-H4 knockdown according to our microarray. These miRNAs are involved in the development of tumors [24-26]. Furthermore, hsa-mir-299-5p , which targets osteopontin, plays a critical role in enhancing proliferation, tumorigenicity, and the ability of spheroid-forming breast cancer cells to display vasculogenic mimicry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we cannot exclude the possibility that miR-31 also contributes to lung cancer metastasis, as elevated levels of miR-31 were associated with patients with lung adenocarcinoma with lymph node metastasis, and this correlated with decreased survival (22). Increased miR-31 levels are also associated with advanced colorectal cancer and lung squamous cell carcinoma and correlated with decreased survival of patients with lung squamous cell carcinoma (18,19). Moreover, our data suggest that SATB2 may be a target of miR-31 in lung cells, and downregulation of SATB2 has been associated with colorectal metastasis (34).…”
Section: Discussionmentioning
confidence: 99%
“…miR-31 is reported to have tumor-suppressing functions, and its expression is decreased during tumorigenesis in several types of cancer, including breast, ovarian, prostate, bladder, hepatocellular, and gastric carcinoma and melanoma (9)(10)(11)(12)(13)(14)(15)(16). In contrast, a proproliferative function for miR-31 was reported in colorectal, head and neck squamous cell, small-cell lung, and esophageal squamous cell carcinoma (13,(17)(18)(19)(20). In the lung, miR-31 overexpression was observed in lung cancers from cyclin E transgenic mice and in 2 of 3 human lung adenocarcinomas and all 3 lung squamous cell carcinomas analyzed (21).…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have demonstrated that HOTAIR is a key regulator of chromatin dynamics and is misregulated in various carcinomas such as urothelial carcinoma [92], pancreatic tumors [93], hepatocellular carcinoma [9497], colorectal carcinomas [98, 99], ovarian cancer tissues [100, 101], sarcomas [102], esophageal squamous cell carcinoma (ESCC) [103106], renal carcinomas [20], nasopharyngeal carcinoma [107], gastrointestinal stromal tumors [82], Laryngeal squamous cell cancer [108, 109], gall bladder cancers [68], nonfunctional pituitary adenoma [110], prostate cancer [111], cervical tumors [109, 112, 113], melanomas [114], gastric cancers [45, 115, 116], Ta/T1 bladder cancer [72] and endometrial tumors [44, 117], (Table 1). Details are summarized below.…”
Section: Hotair and Cancermentioning
confidence: 99%